Utilization of Chia Seeds Powder in Wet Noodle Substituted with Modified Cassava Flour - Matita, Intan Cidarbulan; Soedirga, Lucia Crysanthy; Andriani, Irene (Universitas Sebelas Maret, 2024)
The Indonesian food industry needs to utilize local food commodities as an alternative to wheat, supporting local farmers as part of sustainable agriculture. Modified cassava flour (MOCAF) has similar characteristics to wheat flour yet it lacks gluten and has low protein content. Chia seeds have the potential to improve the textural characteristics of gluten-free products due to their gel-forming ability and are a good source of plant-based protein. This study aims to utilize chia seed powder in the formulation of wet noodles substituted with MOCAF to possibly obtain wet noodles with equal textural characteristics and protein content to 100% wheat flour noodles. In this study, different ratios of wheat flour to MOCAF (100:0, 90:10, 80:20, 70:30, 60:40) and different amounts of chia seed powder (0%, 5%, 10%, 15%) are studied in terms of cooking quality (cooking loss and water absorption), textural properties (hardness, cohesiveness, and chewiness), color (brightness and hue angle). Higher MOCAF substitution resulted in higher water absorption and cooking loss, as well as undesirable (harder) textural properties. Incorporation of chia seeds powder successfully lowers the cooking loss and higher water absorption of the MOCAF-substituted noodles and noodles with 100% wheat flour without chia seeds powder. Chia seed powder can reduce the hardness while maintaining and increasing the chewiness of the MOCAF-substituted noodles. In the MOCAF-substituted noodles, comparable protein content to that of 100% wheat flour noodles can be achieved with the use of 10 to 15% chia seeds powder at a maximum 80:20 substitution ratio.